2016
DOI: 10.1111/ele.12618
|View full text |Cite
|
Sign up to set email alerts
|

How variation between individuals affects species coexistence

Abstract: Although the effects of variation between individuals within species are traditionally ignored in studies of species coexistence, the magnitude of intraspecific variation in nature is forcing ecologists to reconsider. Compelling intuitive arguments suggest that individual variation may provide a previously unrecognised route to diversity maintenance by blurring species-level competitive differences or substituting for species-level niche differences. These arguments, which are motivating a large body of empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
383
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(423 citation statements)
references
References 57 publications
20
383
4
1
Order By: Relevance
“…Further, a reconciliation of the classical niche theory extended in our multidimensional framework with the treatment of 'niche factors' in many modern works (Chase and Leibold 2003) will need to be attempted. Individual variation in the use of different food sources and habitats is unlikely to be independent of measures such as the R* that predict population-level resource consumption, though recent theory suggests that individual variation in either univariate resource use or demographic parameters should make coexistence of competitors less likely (Barab as and D'Andrea 2016, Hart et al 2016). We acknowledge that our framework does not incorporate all current conceptions of the ecological niche, and stress the importance of a broader consideration of the dimensionality of individual niche variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, a reconciliation of the classical niche theory extended in our multidimensional framework with the treatment of 'niche factors' in many modern works (Chase and Leibold 2003) will need to be attempted. Individual variation in the use of different food sources and habitats is unlikely to be independent of measures such as the R* that predict population-level resource consumption, though recent theory suggests that individual variation in either univariate resource use or demographic parameters should make coexistence of competitors less likely (Barab as and D'Andrea 2016, Hart et al 2016). We acknowledge that our framework does not incorporate all current conceptions of the ecological niche, and stress the importance of a broader consideration of the dimensionality of individual niche variation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent theory predicts that individual variation in a single dimension should impede coexistence by causing individuals to compete more strongly with ecologically similar heterospecifics than with dissimilar conspecifics (Barab as and D'Andrea 2016, Hart et al 2016). Recent theory predicts that individual variation in a single dimension should impede coexistence by causing individuals to compete more strongly with ecologically similar heterospecifics than with dissimilar conspecifics (Barab as and D'Andrea 2016, Hart et al 2016).…”
Section: Coexistence and Community Structurementioning
confidence: 99%
“…Specifically, we asked: (a) How consistent are differences in individual specialization across species and communities? We predict that co‐occurring species should present a consistent hierarchy of individual variation across communities (Figure a), which would favour their local coexistence (BarabĂĄs & D'Andrea, ; Hart et al., ). (b) What is the relative importance of intraspecific and interspecific competition, predation and ecological opportunity in explaining the variation of individual specialization across populations?…”
Section: Introductionmentioning
confidence: 93%
“…While evidence is accumulating for intraspecific variation and its ecological significance (Des Roches et al, 2018;Violle et al, 2012), the literature has so far only indicated that coexistence may be weakly facilitated (Lichstein et al, 2007) or further destabilized (Hart et al, 2016) by intraspecific variation. The coexistence mechanism we describe in the context of bacterial systems is in contrast with Hart et al (2016) in that selection is operating in our case and differs from Lichstein et al (2007) in that selection is dynamic.…”
Section: Discussionmentioning
confidence: 99%